Penerapan Teknik Mnemonik Untuk Meningkatkan Penguasaan Kosakata Bahasa Arab Siswa Kelas VIII SMPIT Makassar Islamic School - Nur Iffa Awaliyah; Susiawati Susiawati; Alamsyah Alamsyah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
This article examines the implementation of the Mnemonic technique as a strategy to improve Arabic vocabulary mastery among eighth-grade students at SMPIT Makassar Islamic School. This article specifically aims to identify the planning of the Mnemonic technique implementation, describe the vocabulary learning process using the Mnemonic technique, and analyze the results of its application in improving students’ Arabic vocabulary mastery. Employing a Classroom Action Research (CAR) design, this article was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages, with data collected through observations of teacher and student activities and vocabulary tests administered at the end of each cycle. The results show that the planning of the Mnemonic technique was systematically designed and implemented in line with learning objectives, while the learning process became more active and engaging as indicated by increased student participation. Furthermore, the application of the Mnemonic technique improved students’ Arabic vocabulary mastery, as reflected in the increase of the average score from 84.94% in Cycle I, with 8 out of 17 students not meeting the Minimum Mastery Criterion (MMC), to 88.41% in Cycle II, in which all students met the criterion. In line with these results, teacher and student activity levels also improved from the “fair” category in Cycle I to the “good” category in Cycle II, confirming that the Mnemonic technique is effective in improving Arabic vocabulary mastery among eighth-grade students at SMPIT Makassar Islamic School.